2011
DOI: 10.1111/j.1872-034x.2011.00892.x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of computed tomography imaging features for the diagnosis of autoimmune acute liver failure

Abstract: Heterogeneous hypoattenuation on unenhanced CT was a characteristic CT imaging feature of autoimmune acute liver failure compared with viral ALF. This finding could be one of the tools for diagnosing autoimmune acute liver failure in combination with clinicopathological features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 20 publications
(30 reference statements)
4
56
0
Order By: Relevance
“…Most patients with acute presentation of AIH do not present an elevated immunoglobulin G (IgG) level or high titer of ANA, which is characteristic of AIH . Furthermore, it is often difficult to perform liver biopsy due to the complicated coagulopathy and ascites in patients with acute liver failure . A recent report showed that heterogeneous hypoattenuation on unenhanced CT is a characteristic CT imaging feature of autoimmune acute liver failure compared with viral acute liver failure .…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with acute presentation of AIH do not present an elevated immunoglobulin G (IgG) level or high titer of ANA, which is characteristic of AIH . Furthermore, it is often difficult to perform liver biopsy due to the complicated coagulopathy and ascites in patients with acute liver failure . A recent report showed that heterogeneous hypoattenuation on unenhanced CT is a characteristic CT imaging feature of autoimmune acute liver failure compared with viral acute liver failure .…”
Section: Discussionmentioning
confidence: 99%
“…All laboratory tests and CT scans were obtained at the initial presentation. The presence and patterns of hypoattenuating areas in the liver on the CT scans were subjectively assessed . Liver biopsies were carried out within a week of the referral.…”
Section: Methodsmentioning
confidence: 99%
“…Other than assessing features of portal hypertension, imaging has a limited value as a diagnostic tool in AS‐AIH. Unenhanced computed tomography (CT) can demonstrate heterogenous hypoattenuated regions within the liver in 65% of patients with AIH‐associated ALF when compared with patients with viral‐associated ALF . Liver volume on CT is significantly reduced in nonacetaminophen cases of acute liver injury (ALI)/ALF when compared with acetaminophen‐induced ALI/ALF …”
Section: Epidemiologymentioning
confidence: 99%